Doubling irrigation for southern Africa - do we have enough water and where is the hope? - Xueliang Cai; Chilonda, Pius; Matete, M. (2012)
Southern Africa Development Communality (SADC) through its Regional Indicative Strategic Development Plan (RISDP) has set up an ambitious goal to double irrigation by 2015, which it sees as important component to sustain regional development and ensure food security. While the target timeline is questionable with year 2015 fast approaching, the goal to increase irrigated areas to 7% is certainly valid and has significant implications for regional food security and livelihood of rural population. The objective of this paper is to examine water resources in conjunction with the status of irrigation development in SADC region, and assess water availability for irrigation development. The desktop analysis builds largely upon literature, existing projects and products to integrate baseline information. The results reveal that water is sufficiently available for doubling irrigation without hampering too much on environment even with the possible impacts imposed by climate change. The potential is however largely variable from country to country, and basin to basin. To make irrigation sustainable and cost-benefit effective, irrigation expansion needs to undertake smart water resources/storages development to avoid significant impact on ecosystem functions which are all supported by water.